Phenotypic variation and relationships among sesame（Sesamum indicum L.）sub-core collections - QUENUM Florent J-B; YAN Qi-chuan; GONG Qiu-ju (浙江大学学报. 农业与生命科学版, 2004)
A total of 70 accessions/ecotypes including 50 accessions from the sesame core collection of China and 7 collected in Benin (West Africa) were evaluated for 22 morphological traits, at Zhejiang University, Huajiachi campus, Hangzhou (China). Multivariate and principal component analyses revealed considerable genetic diversity in the material and led to their grouping into 8 clusters. The first two principal components explained 45.2% of the variation. There was no strong relationship between geographic origin and genetic diversity. Seed exchange over short distances and influence of microenvironments may have taken place. Nonetheless, using morphological markers it was possible to group 2 accessions (INRAB-S42 and INRAB-38-1-7) from Benin in cluster Ⅲ, the 6 accessions from Hangzhou (Zhejiang) in cluser Ⅷ; cluster V was formed by accessions from North-East and North-West of China.